1999
DOI: 10.1046/j.1469-7580.1999.19410101.x
|View full text |Cite
|
Sign up to set email alerts
|

The consistent presence of the human accessory deep peroneal nerve

Abstract: Twenty-four human legs were dissected macroscopically to study the morphological details of the accessory deep peroneal nerve. This nerve arose from the superficial peroneal nerve and descended in the lateral compartment of the leg, deep to peroneus longus along the posterior border of peroneus brevis. Approaching the ankle joint, this nerve passed through the peroneal tunnels to wind around the lateral malleolus ; it then crossed beneath the peroneus brevis tendon anteriorly to reach the dorsum of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…A recent anatomical study detected an ADPN in all 24 legs studied; The ADPN consistently gave sensory branches to foot joints and ligaments but innervated the EDB muscle in only 16/24 legs (67%). 6 However, electrophysiological studies reported evidence of ADPN innervating the EDB in 19%-28% of the general population. [7][8][9][10] The reported incidence is higher in studies that routinely applied stimulations behind the lateral malleolus during the performance of peroneal motor conduction studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent anatomical study detected an ADPN in all 24 legs studied; The ADPN consistently gave sensory branches to foot joints and ligaments but innervated the EDB muscle in only 16/24 legs (67%). 6 However, electrophysiological studies reported evidence of ADPN innervating the EDB in 19%-28% of the general population. [7][8][9][10] The reported incidence is higher in studies that routinely applied stimulations behind the lateral malleolus during the performance of peroneal motor conduction studies.…”
Section: Discussionmentioning
confidence: 99%
“…The ADPN consistently sends sensory branches to the ankle joint, tendons and ligaments, motor branches to the peroneus brevis, and occasionally motor branches to the peroneus longus and EDB. 6 The EDB usually extends the second through the fourth toes while the extensor digitorum longus extends the second through fifth toes. The ADPN usually provides only partial innervation of the EDB muscle.…”
Section: Discussionmentioning
confidence: 99%
“…It curled around the lateral malleolus and innervated the extensor digitorum brevis (Ruge, 1878a;Bryce, 1897;Kudoh et al, 1999).…”
Section: Variationsmentioning
confidence: 96%
“…Possible differences in gender and variations in the course of the fibular nerves were taken into consideration and compared with the findings in former literature (Reimann, 1983;Adkison et al, 1991;Kudoh et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, most anatomists, especially Japanese gross anatomists, have observed and discussed anatomical structures and their morphogenesis on the basis of the vertebrate body plan, as described in studies on the limb girdle and forelimb (Aizawa, 1992;Aizawa et al, 1995Aizawa et al, , 1996Aizawa et al, , 1999Akita, 1992aAkita, , 1992bAkita et al, 1992Akita et al, , 1994Akita et al, , 1995Akita et al, , 1999Akita et al, , 2002Arakawa et al, 2005;Aung et al, 2001;Chiba, 1983Chiba, , 1984Chiba, , 1986Chiba, , 1992Chiba et al, 1994;Homma and Sakai, 1991Honma et al, 1998;2003Horiguchi, 1980Horiguchi, , 1981Horiguchi, , 1986Kasai and Yamamoto, 1996;Kasai and Chiba, 1980;Kasai et al, 1989aKasai et al, , 1989bKato andSato, 1978, 1984;Kato, 1989;Kida and Ishida, 1989;Kodama et al, 1992aKodama et al, , 1992bKoizumi, 1989;Koizumi andSakai, 1995, 1997;Koizumi et al, 1999;Kudoh et al, 1999;Kudoh and Saki, 2007;Okamoto et al, 2004;Sato K, 1980;…”
Section: Introductionmentioning
confidence: 99%